Ethiopia in World Athletics - Haile, Prof.SS.Hasrani; Haile, Dr.S.Jayaraman (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
The purpose of this paper is to explore the way in which the known country Ethiopia dominates and shines in the long-distance context. It’s a well-known fact that Ethiopians fixed the foot path strongly in distance races especially Long in International arena. The country has its own unique nature to produce the best runners in Olympics, World Championships, World Cross country races and other International events too. The training environment has its own demographic and biological merits viz. an elevation of 2000 meters above from sea level, obviously which favors for endurance athletes and the morphology of athletes are gifted by birth itself. The existing country produces many Olympians like Abebe Bikila, Mamo Wolde, Derartu Tulu, Fatuma Roba, Haile Gebre Selassie, Kenenisa Bekele, Muruts Yifter, Tirunesh Dibaba and many more. In Ethiopia, long Distance was introduced in the year 1946. Since 1990s, the globe observes the rise of North and East African runners in long distance events which witnessed the birth of a new rising star in the field of long distance running. Kenyan and Ethiopian athletes, in particular, have since remained dominant in these events. Many factors have been proposed to explain the extraordinary success of the Kenyan and Ethiopian distance runners are predetermined physiology, genetics, nutritional aspects, strong morphological factors, well balanced psychological set up, scattered talents and most importantly an urge to boost their economic background. The journey of success of Ethiopia will break the record of 10+25= 45 and this would be uncountable for the forthcoming events.